Determinants of Economic Empowerment and Women’s Roles Transfer - Amiruddin Saleh; Ana Kuswanti; Rita Nur Suhaeti; Alyssa Nahla Amir (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2022)
Women, who were members of Economic Empowerment of Women Headed Family (WHF) Group and married in marital status, still tend to have lower economic status. There was a social reality that roles and functions of husbands and wives in many communities had shifted, especially of WHF Group members in Batang District, Central Java Province. The crucial condition causing the mentioned shifting was economic factors. Formerly, wives were only supporting bread winners, however, because of family economic needs, women switched their roles into breadwinners. Wives also took action as dominant decision makers in their households, although society had not fully recognized woman’s participation in development communication as head of family. The newest finding in this research was that married women, whose husbands had been fired, had already been included into WHF Program. There was 45 percent of WHF Group members, who still got married to husbands with no permanent jobs, and 15 percent belonged to those whose husbands had got fired, and five percent was jobless. The results of FGD supported the finding that there were some married women that had shifted from supporting breadwinners into main breadwinners.